Highly selective synthesis of primary amines from amide over Ru‐Nb2O5 catalysts. Issue 2 (15th December 2021) - Guo, Wanjun; Xia, Qineng; Jia, Hongyan; Guo, Yong; Liu, Xiaohui; Pan, Hu; Wang, Yangang; Wang, Yanqin
Abstract: Amines are an important class of compounds in natural products and medicines. The universal availability of amides provides a potential way for the synthesis of amines. Herein, Ru/Nb2 O5 catalyst is demonstrated to be highly efficient and stable for the selective hydrogenation of propionamide to propylamine (as a model reaction), with up to 91.4% yield of propylamine under relatively mild conditions. Results from XPS analyses, CO chemisorption, TEM images and DRIFTS spectra revealed that the unique properties of Nb2 O5 can effectively activate the C=O group of amides, and the smaller Ru particles on Nb2 O5 could further promote the activation, leading to superior catalytic performance of Ru/Nb2 O5 for amide hydrogenation. Meanwhile, reducing the surface acidity of Nb2 O5 can greatly inhibit the side reactions to by‐products, and further enhance the selectivity to amine. Moreover, this catalytic system is also applicable for the hydrogenation of a variety of amides and provides high potential for the industrial production of primary amines from amides. Abstract : An efficient Ru/Nb2 O5 catalyst for the hydrogenation of propionamide to propylamine with a yield as high as 91.4% is reported.